2021
DOI: 10.1002/1878-0261.13159
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin is a robust prognostic biomarker in colorectal cancer and low expression is associated with sensitivity to inhibitors of topoisomerase, aurora, and HSP90 in preclinical models

Abstract: Cell–cell and cell–matrix adhesion proteins that have been implicated in colorectal epithelial integrity and epithelial‐to‐mesenchymal transition could be robust prognostic and potential predictive biomarkers for standard and novel therapies. We analyzed in situ protein expression of E‐cadherin (ECAD), integrin β4 (ITGB4), zonula occludens 1 (ZO‐1), and cytokeratins in a single‐hospital series of Norwegian patients with colorectal cancer (CRC) stages I–IV (n = 922) using multiplex fluorescence‐based immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 71 publications
1
1
0
Order By: Relevance
“…Our assessment showed that E-cadherin levels were significantly reduced after NACT, confirming the usefulness of E-cadherin as a predictive marker for NACT. This result is consistent with previous studies in BC 39 , 40 , but it is in contrast to results obtained in colorectal cancer where E-cadherin is inversely associated with tumor stage 41 .…”
Section: Discussionsupporting
confidence: 92%
“…Our assessment showed that E-cadherin levels were significantly reduced after NACT, confirming the usefulness of E-cadherin as a predictive marker for NACT. This result is consistent with previous studies in BC 39 , 40 , but it is in contrast to results obtained in colorectal cancer where E-cadherin is inversely associated with tumor stage 41 .…”
Section: Discussionsupporting
confidence: 92%
“…These values were used for the first time for patient grouping. E-cadherin status can impact the response to certain treatments (30,31). For instance, in hormone receptorpositive breast cancers, E-cadherin expression may influence the response to endocrine therapies such as tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…If more than 20% of cancer cells exhibited positive staining in the cytoplasm or nucleus, it was categorized as aberrant expression. Aberrant expression was characterized by the absence of membranous staining and the presence of ectopic expression in the cytoplasm or nucleus [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%